Inibição à corrosão do aço AISI 1020, em meios ácido e salino, por tensoativos e substâncias nitrogenadas microemulsionados - Rossi, Cátia Guaraciara Fernandes Teixeira (2007)
Corrosion inhibition efficiency of saponified coconut oil (SCO) and sodium dodecilbenzene sulfonate (DBS) surfactants in AISI 1020 carbon steel was evaluated by electrochemical methods. These surfactants were also evaluated as microemulsion systems (SCO-ME and DBS-ME), of O/W type (water-rich microemulsion), in a Winsor IV region. They were obtained according to the following composition: 15% SCO, 15% butanol (30% Co-surfactant/Surfactant C/T), 10% organic phase (FO, kerosene) and 60% aqueous phase (FA). These systems were also used to solubilize the following nitrogenated substances: Diphenylcarbazide (DC), 2,4-dinitro-phenyl-thiosemicarbazide (TSC) and the mesoionic type compound 1,3,4-triazolium-2-thiolate (MI), that were investigated with the purpose of evaluating their anticorrosive effects. Comparative studies of carbon steel corrosion inhibition efficiencies of free DBS and DBS-ME, in brine and acidic media (0.5%), showed that DBS presents better inhibition results in acidic media (free DBS, 89% and DBS-ME, 93%). However, the values obtained for DBS in salted solution (72% free DBS and 77% DBS-ME) were similar to the ones observed for the SCO surfactant in brine (63% free SCO and 74% SCO-ME). Analysis of corrosion inhibition of the nitrogenated substances that were solubilized in the SCO-ME microemulsion system by the linear polarization method in brine (0.5% NaCl) showed that such compounds are very efficient an corrosion inhibitors [DC-ME-SCO (92%), TSC-ME-SCO (93%) and MI-ME-SCO (94%)]